Stronger than you know - Foster, Lori, 1958- (Foster, Lori, 1958- McKenzies of Ridge Trail., 2021)
"Reyes McKenzie runs a gym in a run-down part of town where he teaches self-defense and gathers information on illegal activities for his family to investigate. When Kennedy Brooks joins his gym, his concentration is blown to hell. He's never seen a woman work so hard to be lethal...and he wonders what made her that way"--